Awareness and attitude of domestic workers toward COVID-19 and vaccination: a cross-sectional study - Kapoor, Riti Thapar (International Journal Of Community Medicine And Public Health, 2022)
Background: The coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has affected millions of the people all over the world as it was declared as a global pandemic by World Health Organization. The present investigation was conducted in Gejha village of Gautam Buddha Nagar to study the awareness and knowledge level of the domestic workers about COVID-19 and its prevention through vaccination. Methods: Total three hundred participants both male and female were selected for the study. A brief interview and group discussion were conducted with domestic workers and questionnaire was used during the study for analysis of their knowledge about COVID-19. Results: The present study revealed that approximately 98% respondents were aware about the clinical symptoms of COVID-19 and 94% respondents accepted that washing hands, wearing face mask and social distancing are essential to protect against COVID-19. Approximately 98% domestic workers showed their hesitancy for vaccination. They have raised doubts on the efficacy of vaccines and its side effects on health. Conclusions: To fight against pandemic, there is an urgent need of multidimensional approaches and coordinated efforts to address the misconceptions related with the safety and effectiveness of vaccines among the domestic workers.